2010
DOI: 10.1111/j.1751-2824.2010.01370.x
|View full text |Cite
|
Sign up to set email alerts
|

Current status of pathogen inactivation methods

Abstract: Although improved donor selection criteria and tests of increasing sensitivity have dramatically reduced the risks of transfusion‐transmitted infectious disease, multiple potential means exist for a pathogen to escape detection and injure a recipient: a window period remains in which an infectious donor cannot be detected; some transmissions (e.g. bacterial contamination of platelets) have detection methods that are far from the desired capabilities; and ‘emerging’ pathogens continue to represent a risk to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2010
2010
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 56 publications
0
15
1
Order By: Relevance
“…Other experts believe that further RCTs should be conducted before the Intercept system is adopted for routine use [37] because (1) capturing grade 1 (and/or 2) bleeding complications is difficult outside the framework of RCTs [12]; (2) the published surveillance studies [35, 36] that did not report increased bleeding also did not document the increase in platelet transfusions expected from the published RCTs [11]; it is possible that platelet transfusions had been overprescribed before the introduction of the Intercept system, thereby concealing an increased need for platelet transfusions [11] and perhaps also a higher risk of bleeding complications [12] following implementation of pathogen reduction; (3) there is an increase in clinically significant bleeding complications in association with treatment with Intercept when the SPRINT trial data are extracted from the expanded safety analysis of that study [4] (Fig. 2); and (4) in addition to being not blinded, the RCT of Kerkhoffs et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other experts believe that further RCTs should be conducted before the Intercept system is adopted for routine use [37] because (1) capturing grade 1 (and/or 2) bleeding complications is difficult outside the framework of RCTs [12]; (2) the published surveillance studies [35, 36] that did not report increased bleeding also did not document the increase in platelet transfusions expected from the published RCTs [11]; it is possible that platelet transfusions had been overprescribed before the introduction of the Intercept system, thereby concealing an increased need for platelet transfusions [11] and perhaps also a higher risk of bleeding complications [12] following implementation of pathogen reduction; (3) there is an increase in clinically significant bleeding complications in association with treatment with Intercept when the SPRINT trial data are extracted from the expanded safety analysis of that study [4] (Fig. 2); and (4) in addition to being not blinded, the RCT of Kerkhoffs et al.…”
Section: Discussionmentioning
confidence: 99%
“…The RCT of Kerkhoffs et al . [1] questioned prevailing opinion [7–11] that the reduction in post‐transfusion platelet count increments (CCIs) caused by transfusion of platelets treated with Intercept (compared with untreated components) can be overcome by merely increasing platelet transfusions. These investigators [1] demonstrated an increase in bleeding complications in recipients of platelets treated with Intercept compared with controls, despite the fact that the recipients of treated platelets had also received more platelet transfusions to maintain a platelet count of ≥10 000/μl [1].…”
mentioning
confidence: 99%
“…If this is the case, contrary to what we had previously assumed [1,11,12,13], the platelet damage from PR cannot be overcome by merely increasing the platelet dose [14,16]. Introduction of PR in its current stage of development will result in an increase in mild and moderate, albeit perhaps not severe, bleeding complications, which we will have to explicitly tolerate to reap the benefits [1,11,12,13] conferred by PR.…”
Section: Can Pr Be Achieved With a Tolerable Increase In Bleeding Commentioning
confidence: 90%
“…For this reason, AABBaccredited U.S. blood establishments moved voluntarily toward reliance on single-donor platelets so that 87.5% of platelet doses transfused in the U.S. in 2006 were single-donor platelets [10]. In addition, the platelet pathogen-reduction (PR) systems [11,12,13] Intercept and Mirasol®, which use chemicals (respectively, amotosalen HCl along with ultraviolet-A light or riboflavin along with ultraviolet-B light) to inactivate nucleic acids in platelet concentrates, were licensed in Europe for the purpose of confronting the residual risk of TABS and TTIs. Thus, to mitigate the residual risks of TABS and TTIs from platelet transfusion, three alternative risk-reduction strategies may eventually reach the U.S. market: (1) transfusion of already-available non-pathogen-reduced single-donor (as opposed to PWBD) platelets, (2) transfusion of pathogen-reduced single-donor platelets, or (3) transfusion of pathogen-reduced PWBD platelets (if trials of this component are conducted in the U.S. in the future).…”
Section: Introductionmentioning
confidence: 99%
“…However, these observational studies also did not document the expected increase in the number of PLT transfusions owing to the PLT losses caused by PR. Most likely, PLT transfusions had been previously overutilized, so that the effective reduction in PLT dose caused by PR did not result in a visibly increased need for PLTs 10 . It is also possible that the expected increase in mild and moderate (as opposed to severe) bleeding complications might have gone unnoticed outside the framework of an RCT.…”
Section: Period Of Reporting Bleeding Complications In Rcts Of the Hementioning
confidence: 99%